2023
DOI: 10.1093/ecco-jcc/jjad036
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib for Acute Severe Ulcerative Colitis: A Systematic Review

Abstract: Background Tofacitinib has emerged as a new potential treatment for acute severe ulcerative colitis (ASUC). We conducted a systematic review to assess efficacy, safety, and integration in ASUC algorithms. Methods Systematic search in MEDLINE, EMBASE, Cochrane Library, and Clinicaltrials.gov until August 17, 2022, including all studies reporting original observations on tofacitinib for ASUC, preferably defined according to Tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This rate is roughly similar to previous studies on ASUC setting for sequential treatment with IFX‐CyA and vice versa 45 . Although there are limited data for tofacitinib in ASUC in the long term, clinical remission rates of 34% at week 14 have been described, which are slightly lower than our results 41,46,47 . Of note, a recent American study revealed that tofacitinib 10 mg three times daily for the treatment of ASUC was protective against colectomy in bio‐experienced patients 39 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This rate is roughly similar to previous studies on ASUC setting for sequential treatment with IFX‐CyA and vice versa 45 . Although there are limited data for tofacitinib in ASUC in the long term, clinical remission rates of 34% at week 14 have been described, which are slightly lower than our results 41,46,47 . Of note, a recent American study revealed that tofacitinib 10 mg three times daily for the treatment of ASUC was protective against colectomy in bio‐experienced patients 39 …”
Section: Discussionsupporting
confidence: 90%
“…45 Although there are limited data for tofacitinib in ASUC in the long term, clinical remission rates of 34% at week 14 have been described, which are slightly lower than our results. 41,46,47 Of note, a recent American study revealed that tofac- On the other hand, the simultaneous use of corticosteroids, immunomodulators, biologics, and JAK inhibitors, increase the risk of complications and treatment combination or sequencing is frequently needed for ASUC. 51,52 Moreover, high risk of postoperative complications and infections has been observed when colectomy is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…The positive results from the upadacitinib phase III programme in early 2022 may have encouraged pre-licensing use in CD if local policies allowed this. Off-label JAKi use for the treatment of ASUC is unsurprising given the potency and rapidity of onset of JAKi together with the accumulating evidence for their use in this setting [21,22]. Outcomes from the clinical trials of tofacitinib in ASUC are eagerly awaited [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab is the most commonly used rescue agent because cyclosporine is solely an induction agent. In patients with ASUC hospitalized following anti-TNF therapy, observational data demonstrated that tofacitinib may be used as salvage therapy to avoid colectomy (90-day colectomy-free survival of 86%) . Tofacitinib, 10 mg, 3 times daily for 3 days followed by 10 mg twice daily had lower rates of colectomy at 90 days (tofacitinib, 8.3% vs control, 20.4%; hazard ratio, 0.11 [95% CI, 0.02-0.56]); however, randomized trials are required to establish the role of JAK inhibitors in the treatment of ASUC …”
Section: Methodsmentioning
confidence: 99%